Explaining (non) participation: An inquiry on overseas voting of Filipinos in Japan - Jaca, Georgeline B. (Animo Repository, 2018)
This study seeks to examine the problem of low electoral participation of overseas Filipinos in Japan and provide a glimpse on the bigger issue of the perennially low electoral participation of overseas Filipinos around the globe. Ordeshook and Rikers rational model of electoral participation is adopted to illuminate the level of participation of overseas voting Japan during the 2016 national elections by inquiring the perceived benefits, costs, and sense of citizen duty of the overseas Filipinos vis-à-vis the notion of (imagined) homeland attachment. This study employed a convergent mixed methods approach and revealed that low participation of overseas Filipinos do not immediately manifest loss of allegiance to the homeland nor political disinterest; Rather, voting is not seen as an urgent responsibility, albeit acknowledged as a duty. Celebration of identity and exercise of citizenship of the overseas Filipinos in Japan is not limited to the ballot rather expressed in other means such as participation in socio-cultural activities and organizations. Thus while non-participation does not fulfill ones satisfaction from performing the act of an altruistic citizen, it satisfies ones socio-economic needs. Consistent with the assumption of Riker and Ordeshook, this study was able to exhibit that an individual will participate in the elections only when the rewards of voting is greater than the costs. Benefits of participation are less tangible and less direct for overseas voters compared to in-country voters. In relation, the costs of participation for overseas Filipinos in Japan are more substantial and more direct then in-country voters given the limitations of overseas registration and voting. Consequential costs of participation such as lost time and potential income together with the added psychological costs of overseas voting such as issues of insecurity proved to be significant hindrances to participation.